Students Perception on Islamic Psychology and Interest of The Issue on Contemporary Civilization - Fahmi., Reza; Aswirna, Prima (Proceedings of Annual Conference for Muslim Scholars, 2022)
The article discusses the existence of Islamic Psychology amid Western civilization and Eastern civilization (Islam). Where Western Civilization lays the foundation of logical and rational thinking. While on the other hand, Eastern civilization and Islam, prioritize ethics and morals based on normative mindset. Furthermore, there are various contemporary issues of civilization that emerge as evidence of the development of patterns of life, related to the dynamic social changes of today, among others: artificial intelligence, education reform, and digital literacy. Further research is carried out using quantitative approaches. The population in this study were students in four faculties at Imam Bonjol Padang State Islamic University (Faculty of Ushuluddin and Religious Studies, Faculty of Tarbiyah and Teacher Training, Faculty of Da'wah, and Faculty of Sharia), which is as many as 1658 students, using the formula Slovin then, obtained a sample of 322 students. Sample withdrawal is done randomly simply. Data collection is conducted using a scale of psychology, observation, and interviews. The results of this study found a relationship between students' perceptions and their interest in the issues of contemporary civilization. This is shown through r2= 0.875**.